The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.1590/0370-44672021750095
|View full text |Cite
|
Sign up to set email alerts
|

Flexible pavement with mining waste proposal - execution and analysis of an experimental section

Abstract: The extraction of iron ore has a fundamental role in the Brazilian economy. However, such activity generates considerable volumes of waste whose disposal, even if regulated and licensed, has a significant environmental impact. The worldwide concern for sustainable practices along with the urgency for measures to mitigate environmental damage, justifies research on its use in other activities. Therefore, the present study aims to analyze the test results of laboratory versus field of mixtures composed of mining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…There has been early research in the literature on the use of commingled mine wastes as construction materials outside of the mining industry. Andalicio et al [22] experimented with commingled mine waste in base and sub-base layers of experimental roadways. They found that the material behaved differently between laboratory and field settings.…”
Section: Introductionmentioning
confidence: 99%
“…There has been early research in the literature on the use of commingled mine wastes as construction materials outside of the mining industry. Andalicio et al [22] experimented with commingled mine waste in base and sub-base layers of experimental roadways. They found that the material behaved differently between laboratory and field settings.…”
Section: Introductionmentioning
confidence: 99%